Permainan Edukatif Ular Tangga dalam Upaya Meningkatkan Pengetahuan HIV/AIDS Pemuda Desa Towata - Suci Rahmadani; Andi Selvi Yusnitasari; Syamsuar Manyullei; Dian Saputra Marzuki; Muhammad Yusri Abadi (Universitas Mathla'ul Anwar Banten, 2020)
EDUCATIVE GAMES OF GIANT SNAKE IN THE EFFORTS TO INCREASE THE TOWATA VILLAGE YOUTH HIV/AIDS KNOWLEDGE. HIV (Human Immunodeficiency Virus) is a virus that attacks white blood cells in the body and results in the decline of human immunity. This is one of the problems of adolescent's premarital sexual behavior and abuse of drug use, many adolescents are still lacking knowledge about the dangers of HIV and not infrequently also as adolescents already know the negative effects but do not think about future risks. The aim of this intervention is to increase the understanding of village youth regarding the importance of avoiding anything that can lead to HIV and stigmatizing the community to avoid the disease rather than the person. The method used in this counseling is the Educational Giant Ladder Snake Faith to increase knowledge about HIV. The implementation technique is to go to the village youth gathering place and encourage them to take part in the eductive faith of the giant ladder snake. The evaluation method is carried out by holding a pre-test and post-test. The results show that there is a difference in the increase in knowledge before and after the game with an average of 5.70 to an average of 7.20. It is expected that young people can apply the knowledge that has been obtained during the game to be able to avoid risky behaviors of transmitting HIV/AIDS and can eliminate the negative stigma of society against disease and people with HIV/AIDS.